(3x-2y4)-3 =

(3x-2y4)-3 =

Input
(3 x – 2 y^4) – 3
Result
3 x – 2 y^4 – 3
Polynomial discriminant
Delta_y = -55296 (x – 1)^3
Integer root
x = 54 n^4 + 1, y = 3 n, n element Z
Derivative
(d)/(dx)((3 x – 2 y^4) – 3) = 3
Indefinite integral
integral (-3 + 3 x – 2 y^4) dx = (3 x^2)/2 – 2 x y^4 – 3 x + constant
Definite integral over a square of edge length 2 L
integral_(-L)^L integral_(-L)^L (-3 + 3 x – 2 y^4) dy dx = 2 L (-(4 L^5)/5 – 6 L)

Leave a Reply

Your email address will not be published. Required fields are marked *